Map of Employer Needs and Young IT Professionals - Zholdasbekova, Gulbakhyt; Karimova, Madina; Duisebayeva, Aizhan; Abdulina, Gulnar (Journal of Technical Education and Training, 2024)
The increasing prevalence of unemployment in the Mangistau and West Kazakhstan regions necessitates the exploration of alternative pathways for professional development among young individuals in the process of selecting their specialties, as well as among older individuals considering retraining options. Digitalization emerges as the most promising avenue for such development. This research aims to identify the specific needs of young people in the Mangistau and West Kazakhstan regions during their job search in the IT field and determine the IT professions in high demand according to employers. The research employs online surveys and economic-statistical analysis as the primary methods. The findings indicate that the negative labor market trends in Kazakhstan and neighbouring countries are projected to worsen by 2030. Furthermore, while the information and communication technology sector represent a highly promising area for new job creation, employers’ expectations often do not align with the skill sets possessed by young professionals. Employers also anticipate a future surge in demand for cybersecurity specialists. The practical significance of this research lies in enabling young applicants to make informed decisions regarding their IT career paths, allowing employers to gain insight into the expectations of potential employees, and aiding public authorities in developing education and IT programs to combat youth unemployment. The findings obtained can be adapted to suit the requirements and developmental levels of other countries worldwide, and can be applied in practice to enhance the effectiveness of IT education.